Sexuality after stroke: patient counseling preferences. - Stein, Joel; Hillinger, Marni; Clancy, Cait; Bishop, Lauri (Disability & Rehabilitation, 2013)
Purpose: Sexual dysfunction is common after stroke, but is frequently not addressed by healthcare providers. The aim of this study was to examine patient preferences for counseling related to sexuality post-stroke. Method: Two hundred and sixty-eight patients from a stroke registry were provided an anonymous paper or online survey. Thirty-eight patients responded and completed the survey. The survey included demographic information, and scales of sexual dysfunction, fatigue, depression and functional independence. In addition, we queried subjects about stroke-related sexual dysfunction and their preferences for counseling and education materials. Results: Most respondents (71%) identified sexuality as a moderately to very important issue in their post-stroke rehabilitation. Sexual dysfunction was common, with 47% of respondents indicating that their sexual function had declined since the stroke. Eighty-one percent reported receiving insufficient information about sexuality post-stroke, and the majority (60%) expressed a preference for receiving counseling regarding sexuality from a physician. A substantial portion (26.5%) of patients wanted to receive counseling prior to discharge from a hospital or rehabilitation center, with 71% wishing to receive counseling within 1 year post-stroke. Conclusions: Many stroke survivors experience sexual dysfunction and indicate a desire for additional information and counseling from healthcare providers. Preferences regarding the timing of such counseling vary, creating challenges for optimizing the delivery of this care.